Artificial Intelligence and Its Impact on Enhancing Women’s Health and Medical Condition Monitoring. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Artificial intelligence (AI) is revolutionizing healthcare, particularly in the field of disease detection. AI-powered algorithms can analyze vast datasets of medical images, patient records, and genetic information to identify patterns and predict disease risks with unprecedented accuracy. In women's health, AI applications are proving particularly promising in areas such as breast cancer detection, early diagnosis of ovarian cancer, and prenatal risk assessment. AI-powered imaging analysis can significantly improve the accuracy and efficiency of mammograms and ultrasounds, leading to earlier detection and improved treatment outcomes. AI algorithms can also analyze a woman's medical history, lifestyle factors, and genetic predisposition to predict her risk of developing certain diseases and personalize preventive care strategies. As AI continues to evolve, it holds immense potential to transform women's healthcare by enabling earlier detection, more accurate diagnoses, and more personalized treatment plans, ultimately improving women's health outcomes and longevity.